Tax Incentives and MSME Growth: Empirical Evidence from Indonesian Small Businesses - Loso Judijanto; Ahmad Junaidi; Azimah Hanifah; Junet Kaswoto; Inneke Respatiningsih (Westscience Press, 2026)
This study investigates the impact of tax incentives and financial literacy on the growth of Micro, Small, and Medium Enterprises (MSMEs) in Indonesia. A quantitative approach was employed, surveying 175 MSME owners using a Likert scale questionnaire. The data was analyzed using SPSS version 25, with descriptive statistics, correlation analysis, and multiple regression analysis conducted to examine the relationships between the independent variables (tax incentives and financial literacy) and the dependent variable (MSME growth). The results show that both tax incentives and financial literacy positively affect MSME growth, with financial literacy having a slightly stronger influence. Tax incentives provide financial relief, enabling MSMEs to reinvest in their businesses, while financial literacy equips business owners with the knowledge needed to make informed decisions. The study highlights the importance of integrating tax incentive awareness and financial literacy programs to promote sustainable growth and competitiveness in MSMEs. Policy recommendations include simplifying tax procedures, increasing awareness of available incentives, and enhancing financial education programs for MSME owners.